(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
The article is devoted to the structural description of the dictionary of the winged words used in the modern literary German language. It is suitable for the Belarusians studying German as a foreign language. It shows texts as a source of winged words in the German language; principles of dictionary building, its volume; besides there are examples of lexicographic description of the winged words dating back to the proper German sources. Each and every German winged word in the dictionary has an equivalent from the Belarusian language. Therefore, the dictionary can be useful for the Germans studying Belarusian as well. The dictionary is intended for specialists in the phraseology of Germanic languages, university students and teachers, secondary school students and teachers, editors and translators, as well as anyone who learns German as a foreign language, but can also be useful for German speakers as a normative linguistic reference. The dictionary can be effectively used in the educational process when teaching German as a foreign language in higher and secondary educational institutions, as well as as a guide in the study of vocabulary and phraseology of the modern German literary language and in the preparation of term papers and diplomas in the German language (history of the German language, phraseology and paremiology of the German language, the style of the German language). The dictionary can be used as a lexicographic base for compiling the German-Belarusian dictionary of winged words and the Belarusian-German dictionary of winged words.